THE EMERGENCE OF EARLY TETRAPODS - Clack J.A. (My University, 2006)
Study of Devonian tetrapods and their relatives spanning the so-called 'fish-tetrapod' transition has expanded almost exponentially in the last 15 years or so. This evolutionary event is now represented by at least nine named genera of Devonian tetrapod, several new 'near-tetrapods' and a number of new tetrapods from the Early Carboniferous. The anatomy of Acanthostega has radically changed ideas about how this transition took place, and more recently the anatomy of Ichthyostega is being reassessed with some startling conclusions such as the unique construction of its ear region. The current state of research on this range of animals is summarized, followed by a consideration of the acquisition of limbs and digits among tetrapods including their possible forerunners, the development of digits and their original function, and the onset of pentadactyly. The faunal relations and palaeoecological contexts of the Devonian tetrapods are brought together in an initial though necessarily brief survey, followed by an assessment of Devonian tetrapod diversity, which is seen to be much greater than previously realised. Finally, some hopes and ambitions for the future are set out. © 2005 Elsevier B.V. All rights reserved.
Keywords: CARBONIFEROUS; DEVONIAN; EVOLUTION; FISH-TETRAPOD TRANSITION; PALAEOENVIRONMENTS; TETRAPODOMORPHS; TETRAPODS; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Devonian; Палеозой::Девонская